A simple 2D composite image analysis technique for the crystal growth study of L‐ascorbic acid. Issue 6 (17th January 2017) - Kumar, Krishan; Kumar, Virender; Lal, Jatin; Kaur, Harmeet; Singh, Jasbir
Abstract: This work was destined for 2D crystal growth studies of L‐ascorbic acid using the composite image analysis technique. Growth experiments on the L‐ascorbic acid crystals were carried out by standard (optical) microscopy, laser diffraction analysis, and composite image analysis. For image analysis, the growth of L‐ascorbic acid crystals was captured as digital 2D RGB images, which were then processed to composite images. After processing, the crystal boundaries emerged as white lines against the black (cancelled) background. The crystal boundaries were well differentiated by peaks in the intensity graphs generated for the composite images. The lengths of crystal boundaries measured from the intensity graphs of composite images were in good agreement (correlation coefficient " r " = 0.99) with the lengths measured by standard microscopy. On the contrary, the lengths measured by laser diffraction were poorly correlated with both techniques. Therefore, the composite image analysis can replace the standard microscopy technique for the crystal growth studies of L‐ascorbic acid. Abstract : Composite images were prepared from original RGB images. The crystal boundaries were easily identifiable and quantifiable in composite images. The correlation results confirmed the suitability of the composite image analysis technique.